Development Of Food Ordering Web Based System for Restaurant - TONG, BOON LOKE; SAMSUDIN, NOOR AZAH (Applied Information Technology And Computer Science, 2022)
The Food Ordering System is developed in web-based system with simplified and neat interface for easier the user to use this system. Since the people nowadays are busying all the time and do not much time to dine in the restaurant, so the Food Ordering System can help them to order food online. There is some problem suffer by the owner and customer of the restaurant. Before using this Food Ordering System, the manual filing system is using before using food ordering system. The staff of restaurant is using the pen and calculator to record and calculate the total amount of order. The objective of the Food Ordering System is to identify the problems of existing food ordering, to design a food ordering system and to evaluate the food ordering system. The object-oriented approach used for developed the Food Ordering System such as use case diagram, sequence diagram and activity diagram. The Food Ordering System will be developed according to the agile model. The Gantt chart will be produced to record the project timeline. The proposed system can be used by the worker of the restaurant and the customer of restaurant. The owner and the worker can take order of the customer through online or offline in the restaurant. The customer can make order through the system online by delivery or self-collect. The owner can also manage the menu and the order of the customer. This system will increase the efficiency of the restaurant in ordering the food of the customer and also will help the management of the restaurant more systematically.